2019
DOI: 10.1002/ehf2.12456
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Doppler blood pressure measurement in continuous‐flow left ventricular assist device patients

Abstract: Aims Accurate blood pressure (BP) measurement in continuous‐flow ventricular assist device (CF‐VAD) patients is imperative to reduce stroke risk. This study assesses the accuracy of the Doppler opening pressure method compared with the gold standard arterial line method in CF‐VAD patients. Methods and results In a longitudinal cohort of HeartMate II and HVAD patients, arterial line BP and simultaneously measured Doppler opening pressure were obtained. Overall correlation, agreement between Doppler opening pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…60 Doppler ultrasound with sphygmomanometer is most frequently used and its measurements closely reflect arterial-line MAP but they also reflect systolic blood pressure in cases of high pulse pressure. 61 Overall, Doppler opening blood pressure has good correlation with MAP even with higher pulse pressures. The main issue with Doppler-derived BP measurements is that it is impractical for home blood pressure monitoring.…”
Section: Hypertension In Lvad Patientsmentioning
confidence: 87%
“…60 Doppler ultrasound with sphygmomanometer is most frequently used and its measurements closely reflect arterial-line MAP but they also reflect systolic blood pressure in cases of high pulse pressure. 61 Overall, Doppler opening blood pressure has good correlation with MAP even with higher pulse pressures. The main issue with Doppler-derived BP measurements is that it is impractical for home blood pressure monitoring.…”
Section: Hypertension In Lvad Patientsmentioning
confidence: 87%
“…To answer these questions, a previous large, prospective study examined the accuracy of Doppler BP in continuous flow VAD patients implanted with the HeartMate II and the HeartWare HVAD. 12 For these two devices, Doppler BP was very accurate when compared with arterial line MAP as the gold standard and maintained its accuracy over a wide range of pulse pressures.…”
Section: Introductionmentioning
confidence: 90%
“…For consistency, this study was carried out, and data were analysed in a similar fashion to our previously published study on Doppler BP in HeartMate II and HVAD patients. 12 During the study period, non-invasive BP measurements in VAD patients were prospectively obtained by Doppler opening pressure per institutional protocol. When study patients had an arterial line placed for intra-arterial BP monitoring for any clinical indication, both arterial line pressures and Doppler opening pressure were taken and recorded.…”
Section: Methods Samplementioning
confidence: 99%
“…The ENDURANCE Supplemental trial showed that a blood pressure management protocol targeting a mean arterial pressure (MAP) of less than 85 mmHg significantly reduced stroke, especially hemorrhagic stroke, rates (Milano et al 2018). It has also been shown in CF-VAD patients that Doppler opening pressure is a highly accurate estimate of MAP and should be used as the default noninvasive BP measurement method (Li et al 2019). In addition, in the course of the HeartWare ADVANCE BTT + CAP trial, a protocol change requiring high-dose aspirin 325 mg daily and an INR goal range of 2.0-3.0 reduced ischemic stroke rate without increasing hemorrhagic stroke rate (Slaughter et al 2013).…”
Section: Management Of Patients On Btt Vadmentioning
confidence: 99%